- Cost Driver of Diabetes Mellitus Care in JKN Healthcare Facilities: A Case Study from Indonesia: - - Gunawan, Susilawati (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Background: Diabetes Mellitus is one of the most serious global health issues, with a sharply increasing healthcare cost burden, particularly in low- and middle-income countries such as Indonesia. Research on the determinants of DM treatment cost in JKN-affiliated healthcare facilities in Indonesia remains limited. Purpose: This study aims to analyze the factors influencing variations in the treatment costs of diabetes mellitus patients at advanced referral healthcare facilities under JKN scheme. Method: This research employed a quantitative analytical observational design with a cross-sectional approach. Data were obtained from a sample of JKN patients in 2021, comprising 25,539 primary DM cases. Statistical analysis was performed using the Kruskal-Wallis and Mann-Whitney tests with a significance level of p<0.05 to examine length of stay, type of healthcare facility, type of clinical intervention, disease severity, region, referral pattern, and JKN membership classification Result: The average treatment cost for DM was IDR 2,512,968, while the weighted average cost was IDR 25,600,935. Statistically significant variations in treatment costs were identified across all independent variables. Factors such as prolonged length of stay, higher disease severity, intensive clinical interventions, and referral to tertiary care facilities were associated with increased treatment costs. Regional disparities were also observed, with the highest treatment cost found in provinces on Java Island. Conclusion: Effective management of DM treatment costs in Indonesia requires a regionally based approach, risk stratification according to service complexity, and the optimization of healthcare facility and workforce distribution. Strengthening preventive and promotive health programs is crucial to reducing long-term treatment costs. Keywords: diabetes mellitus, treatment costs, national health insurance, cost variation analysis, Indonesia